MAGENTA: a Multinational patient survey assessing the Awareness, perceptions and unmet needs in GENetic Testing and counselling among patients with breAst cancer - Powell, Sarah; Artigas, Marta; Borovova, Irina; Gadiya, Poorva; Hsu, Alice; Kaur, Ranjit; Kidd, Lisa; Rosenfeld, Denise; Saeed, Mai Mohamed; Scarelli, Evelin; Youssef, Magdy Waheeb (Frontiers in Oncology, 2024)
Objective: Genetic testing and counselling are critical in assessing breast cancer risk and tailoring treatment strategies. However, several barriers hinder patients from opting for genetic testing/counselling, leading to fewer than one-third of patients undergoing testing and even fewer being offered counselling. A granular understanding of these barriers is essential in overcoming them. Methods: A multinational survey developed by patient authors was conducted in 9 countries, to identify the specific local/regional barriers. The survey question pathway was individualized, based on responses to prior questions. Percentage responses to a response option were calculated based on the total number of respondents to that question. Chi-square tests were used to assess the significance of the results, if applicable. Results: The final analysis set (FAS) included 1,176 respondents, with a subset of this responding to all questions. In the FAS, 63% of respondents had undergone testing. Among those who got tested, 70% were offered testing. Among untested respondents, only 40% were offered the test but eventually did not get tested. In the tested population, 44% received counselling, which was significantly higher than 7% (p<0.00001) in the untested group. Among those reporting on awareness, 71% reported awareness level between ‘very low’ and ‘moderate’ prior to cancer diagnosis. Most respondents (71%) agreed that all breast cancer patients should undergo testing before treatment initiation. However, Asian patients were less likely to endorse this view compared to respondents from other regions (25% vs ≥50%; p<0.00001). A higher proportion of tested respondents were ‘very willing’ to get their family members tested (44%) versus untested respondents (11%), with relatively higher willingness among Australian (77%) and Russian respondents (56%), the regional variation being statistically significant (p<0.00001). Conclusions: Critical gaps remain in the access, awareness and perceived value of genetic testing and counselling, with regional variance or difference between the tested and untested groups. Most patients are not offered counselling, which may be associated with the low uptake of testing. Strategic action is needed to drive policy-shaping and improve access to testing and counselling, including raising patient awareness and improving patient experience for better treatment outcomes.